2009
DOI: 10.1086/605675
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hepatitis B Virus Infection on Human Immunodeficiency Virus Response to Antiretroviral Therapy in Nigeria

Abstract: Background As HAART is introduced into areas of the world with high hepatitis B virus (HBV) endemicity, it is important to determine the influence of HBV on HIV-HBV co-infected persons receiving antiretroviral therapy (ART). Methods We studied 1,564 HIV-infected subjects in Jos, Nigeria who initiated ART. HIV-HBV co-infected participants had HBeAg and HBV DNA status determined. CD4+ T-cell count and HIV viral load at ART initiation were compared between HIV mono-infected and HIV-HBV co-infected subjects usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
93
6
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(126 citation statements)
references
References 19 publications
26
93
6
1
Order By: Relevance
“…Elevated ALT and AST levels were also more common in patients with immunologically defined AIDS compared to patients with CD4 + T lymphocyte counts > 200 cells/mm³, and this represents about 21% and 31% of total patients with elevated ALT and AST levels respectively. Idoko et al, (2009), observed 18% of the cohort with elevated ALT levels in their study [8] and this is comparable to the value obtained in the current study. Higher mean and elevated ALT and AST levels among immunologically defined AIDS patients is not unexpected as some opportunistic infections in AIDS patients may secondarily infect liver cells and result to high hepatic transaminases levels due to liver cell injury.…”
Section: Distribution Of Hbsag Mean Cd4 + T Cell Countssupporting
confidence: 91%
See 1 more Smart Citation
“…Elevated ALT and AST levels were also more common in patients with immunologically defined AIDS compared to patients with CD4 + T lymphocyte counts > 200 cells/mm³, and this represents about 21% and 31% of total patients with elevated ALT and AST levels respectively. Idoko et al, (2009), observed 18% of the cohort with elevated ALT levels in their study [8] and this is comparable to the value obtained in the current study. Higher mean and elevated ALT and AST levels among immunologically defined AIDS patients is not unexpected as some opportunistic infections in AIDS patients may secondarily infect liver cells and result to high hepatic transaminases levels due to liver cell injury.…”
Section: Distribution Of Hbsag Mean Cd4 + T Cell Countssupporting
confidence: 91%
“…Idoko et al, (2009) in their studies observed similar finding with regard to CD4 + T cell counts, however observed significant difference in relation to ALT levels [8] . Olawumi et al, (2014) in their studies documented similar results with regard to CD4 + T cell counts and AST levels [9] .…”
Section: Distribution Of Hbsag Mean Cd4 + T Cell Countsmentioning
confidence: 51%
“…Areas where HBV is highly endemic usually overlap with areas having high rates of HIV infection [10]. Being a moderate HBV endemic country having a large population of people living with HIV/AIDS, India presents an ideal setting for increased transmission and occurrence of HIV-HBV co-infections.…”
Section: Introductionmentioning
confidence: 99%
“…This is because CHB is a disease that requires adequate explanation, counseling, and individualized assessment for successful anti-HBV therapy. The Society for Gastroenterology and Hepatology in Nigeria identified this lack of knowledge among health care providers and took a positive step towards addressing the situation by publishing the first edition of a treatment guideline for Hepatitis B and C in Nigeria in 2009 (10). The circulation of this document needs to be widened so that doctors and other health workers will begin to implement the guideline provisions.…”
Section: Public Awareness and Educationmentioning
confidence: 99%
“…Over 70% of the population shows evidence of past infection with the virus and 7.3-24% of the population has serological evidence of current infection (average 13.7%). Thus, 19 million Nigerians are currently infected and approximately 5 million will die of causes related to HBV infection (10).…”
Section: Introduction and Epidemiologymentioning
confidence: 99%